A chiral enantioseparation generic strategy for anti‐Alzheimer and antifungal drugs by short end injection capillary electrophoresis using an experimental design approach. Issue 2 (20th November 2017) - Abdel‐Megied, Ahmed M.; Hanafi, Rasha S.; Aboul‐Enein, Hassan Y.
Abstract: The present study describes a generic strategy using capillary electrophoretic (CE) method for chiral enantioseparation of anti‐Alzheimer drugs, namely, donepezil (DON), rivastigmine (RIV), and antifungal drugs, namely, ketoconazole (KET), Itraconazole (ITR), fluconazole (FLU), and sertaconazole (SRT) in which these drugs have different basic and acidic properties. Several modified cyclodextrins (CDs) were applied for enantioseparation of racemates such as highly sulfated α, γ CDs, hydroxyl propyl‐β‐CD, and Sulfobutyl ether‐β‐CD. The starting screening conditions consist of 50‐mM phosphate‐triethanolamine buffer at pH 2.5, an applied voltage of 15 kV, and a temperature of 25°C. The CE strategy implemented in the separation starts by screening prior to the optimization stage in which an experimental design is applied. The design of experiment (DOE) was based on a full factorial design of the crucial two factors (pH and %CD) at three levels, to make a total of nine (3 2 ) experiments with high, intermediate, and low values for both factors. Evaluation of the proposed strategy pointed out that best resolution was obtained at pH 2.5 for five racemates using low percentages of HS‐γ‐CD, while SBE‐β‐CD was the most successful chiral selector offering acceptable resolution for all the six racemates, with the best separation at low pH values and at higher %CD within 10‐min runtime. Regression study showed that the linear model shows a significant lack of fit for all chiral selectors, anticipating that higher orders of the factors are most likely to be present in the equation with possible interactions. Abstract :